(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Addressing the themes of death and mourning is not an easy task, although indispensable for psychologists. These issues become even more relevant in situations of great crisis (as in a pandemic context) and also when we talk about the death of famous people, because of the commotiongenerated by the loss. Grief is a complex behavioral process and, in its treatment, the individual must accept the reality of the loss and learn to live in a world without the physical presence of that person, coming into contact with new drivers. The writing of this article was motivated by the sad departure of João Claudio Todorov, behavior analyst, professor, manager, popularizer of science. The writing of this article was motivated by the sad departure of João Claudio Todorov, behavior analyst, teacher, manager, science disseminator. The writing of this article was motivated by the sad departure of João Claudio Todorov, behavior analyst, teacher, manager, science disseminator. His trajectory has been and will continue to be inspiring to behavior analysts for a long time and is therefore briefly mentioned in the following article. We hope to keep in touch with your legacy, and that this continues to influence so many professionals in our field.